Fundamental Education: UNESCO and American Post-War Modernism - Matthew Chambers (Transatlantica)
This article examines how the impact of modernism’s reception dominated post-war poetic discourse, and in turn, how the intersection of literary and political interests in the late 1940s resulted in an education platform with a global reach and implications, mainly in the form of non-governmental organizations (NGOs), and most notably in the shaping of UNESCO. The rise of literary and cultural NGOs, then, is best viewed in light of an intersection of political and academic interests that institutionalized literary production in the form of humanitarian outreach. The claims for modernism’s liberatory aesthetics were folded into a discourse of cultural freedom that was packaged as an educational imperative for global literacy. I.A. Richards and Archibald MacLeish’s different involvements in UNESCO will be used as case studies to illustrate how one aspect of modernism’s transmutation into a populist progressive political discourse occurred and how they reflected a global structural shift for literary production.